CODE - SWITCHING OF ENGLISH IN THE ENTERTAINMENT PROGRAM OF SARAH SECHAN SHOW IN NET TV - Eva Nurul Chandra; Risa Mufliharsi (Deiksis, 2015)
The main purpose of the study was to identify the code – switching that used by Sarah Sechan in the entertainment program of Sarah Sechan Show in NET TV episode “ Joe Taslim “ and “ Coky Sitohang”. What are the factors that can influence the presenter in using code-switching to her quest . Qualitative study based on participant observation, recording technique and note – talking. In this study, reserchers found 2 ( two ) kinds of code-switching, such as : methaporical code-switcing and situational code-switching.Key words : Code-switching, Entertainment program, Sarah Sechan.